Photoinitiation rate profiles during polymerization of a dimethacrylate-based resin photoinitiated with camphorquinone/amine. Influence of initiator photobleaching rate - Asmussen, Silvana Valeria (2009)
The photodecomposition of camphorquinone (CQ)/amine during the photo polymerization of a dimethacrylate-based resin under continuous irradiation was investigated in thick samples. The global CQ photoconsumption was measured by monitoring the decrease in light absorption as a function of irradiation time and the kinetics were satisfactory fitted to a first order expression where the rate constant of photobleaching was proportional to the irradiation intensity. In a thick sample, the photobleaching of the photoinitiator is accompanied by a deeper penetration of the light through the underlying layers. These gradients of photoinitiator concentration, light intensity and photoinitiation rate along the path of irradiation were calculated. The photodecomposition reaction was spatially inhomogeneous and the degree of nonuniformity increased with increased initial sample absorbance. The influence of the photobleaching process on the polymerization reaction was examined. The photobleaching rate of CQ was much slower than the polymerization rate and only 20% of the initial amount of CQ was consumed before the polymerization reaction had almost ceased. Results obtained in this research highlight the inherent interlinking of light attenuation and photobleaching rate in bulk polymerizing systems. © 2008 Elsevier Ltd. All rights reserved.